887 Care Co-ordination for children with a disability or developmental difficulty empowers families and reduces the burden on staff supporting them. (17th August 2022) - Myers, Sarah; Collins, Bethan; Maguire, Sabine
Abstract : Aims: Of the estimated 800, 000 children and young people (CYP) with a disability or developmental difficulty (DDD) living in the United Kingdom (UK), almost half will have input from more than one professional at a time. Parents of these CYP may experience elevated stress, poor health and are vulnerable to economic difficulties leading families to experience detrimental impacts on their health outcomes, family functioning and wellbeing. Greater integration and coordination of care have been recommended to improve health service cost-effectiveness, service-user experience and to better address unmet needs. Care Coordination (CC) aims to provide a single point of contact and a coordinated service, thereby improving care experiences, meeting unmet needs and empowering families ( figure 1 ). The voices of families of children with DDD relating their experiences of CC are lacking in the literature. We aim to determine the experiences of parents, and professionals supporting them, accessing a CC service in South Wales, UK. Methods: Between May and August 2020, an in-depth evaluation of CC in Gwent, South Wales was conducted. Of the 284 families who accessed CC, 38 were approached, as well as 177 health and social care professionals based at Serennu, Nevill Hall and Caerphilly Children's Centres. Nine families and 14 professionals completed semi-structured interviews. Interview transcripts were analysed using qualitative data analysis software, NVivo (QSR International). Inductive thematic analysis was used for identifying, analysing and reporting patterns within the data. The data was double coded by two researchers, neither of whom are involved in CC service delivery. Ethical approval was given by Aneurin Bevan University Health Board Research and Development Department Risk Review Panel. Results: This evaluation found perceived improvements in families' abilities to navigate, organise and understand care, and increased parental engagement with healthcare services following CC involvement ( figure 2 ). The relationship between families and Care Coordinators was described as 'empowering' and it was found to be beneficial that Care Coordinators are not 'clinical' professionals, making them more approachable. CC also provided families with a single point of contact. Families and professionals observed increased engagement in healthcare following intervention from CC; families felt CC helped them regain control of their child's healthcare and explore potential barriers to engagement, and professionals observed fewer missed appointments. Participants suggested CC improved multidisciplinary working and helped facilitate joint appointments, and both professionals and families described CC as a source of holistic support, including practical advice regarding housing and finances and emotional support. Professionals commented on CC easing pressure on their service to provide informal support for families, in addition to their work. Potential limitations of CC included restricted staff capacity, and the role not being defined clearly for families and professionals. Conclusion: At a time of increased stress for families of CYP with DDD, and scarce resources to support them, Care Coordinators play a vital role in assisting families to engage with health services, and enabling them to feel supported and empowered. This service reduces the burden on professionals, whilst enhancing relationships with the families.